Parental Expressions of Anxiety and Child Temperament in Toddlerhood Jointly Predict Preschoolers' Avoidance of Novelty. (21st December 2018) - Aktar, Evin; Majdandžić, Mirjana; De Vente, Wieke; Bögels, Susan M.
Abstract : This study investigated the link between (a) parents' social trait and state anxiety and (b) children's fear and avoidance in social referencing situations in a longitudinal design and considered the modulating role of child temperament in these links. Children were confronted with a stranger and a robot, separately with their father and mother at 1 ( N =  122), at 2.5 ( N =  117), and at 4.5 ( N  = 111) years of age. Behavioral inhibition (BI) was separately observed at 1 and 2.5 years. Parents' social anxiety disorder (SAD) severity was assessed via interviews prenatally and at 4.5 years. More expressed anxiety by parents at 4.5 years was not significantly linked to more fear or avoidance at 4.5 years. High BI children were more avoidant at 4.5 years if their parents expressed more anxiety at 2.5 years, and they were more fearful if the parents had more severe forms of lifetime SAD. More severe lifetime forms of SAD were also related to more pronounced increases in child fear and avoidance over time, whereas parents' expressions of anxiety predicted more pronounced increases in avoidance only from 2.5 to 4.5 years. High BI toddlers of parents with higher state and trait anxiety become more avoidant of novelty as preschoolers, illustrating the importance of considering child temperamental dispositions in the links between child and parent anxiety. Moreover, children of parents with more trait and state anxiety showed more pronounced increases in fear and avoidance over time, highlighting the importance of early interventions targeting parents' SAD.